Orientations of preservice teachers' practical knowledge during school placement: Concept mapping as a reflective tool. Issue 3 (4th May 2022) - Wei, Ge; Lu, Litao
ABSTRACT: School placement is a critical part of initial teacher education (ITE) that provides authentic contexts in which preservice teachers (PSTs) can bridge theory and practice. This paper presents an exploratory study of PSTs' practical knowledge orientations during a six-week school placement. As a reflective tool, concept mapping helped the nine Chinese PSTs probe the orientations of their practical knowledge. The follow-up interviews strengthened our findings of the following three orientations of PSTs' practical knowledge: interpersonal-interaction-oriented, problem-solving-oriented, and professional-identity-oriented knowledge. Based on the participants' annotation, the differences in the PSTs' knowledge orientations are influenced by their prior teaching experience, received mentoring, and critical events during placement. This study provides transnational implications for developing PSTs' practical knowledge with reflection by using concept mapping during on-site practice.